A study evaluating the relationship between phubbing levels and empathic attitudes of college students - Uncu, Fatos; Güneş, Dilek; Kılınç, Nur Özlem; Güneş, Muhammet Emin (My University, 2024)
The objective of this research is to investigate the relationship between phubbing levels and the empathy attitude of college students. In our descriptive and correlational study, data were gathered from 528 college students studying in the undergraduate program of a university in Eastern Türkiye. Personal information form, Phubbing Scale, and Empathic Tendency Scale were employed as data collection forms. The research’s findings were examined using the SPSS 22.00 package program, and all analyses were judged significant if the p-value is less than 0,05 (p<0.05). The average total scores of the college students were found to be 42.77±19.09 on the Generic Scale of Phubbing (GSP) and 62.52±7.56 on the Empathic Tendency Scale (ETS). We found a significant difference between the mean phubbing and empathic tendency scores of college students and the number of book readings per week, the number of friends, and the meeting with friends weekly. The conclusion was that there was a strong negative and significant association between students’ total mean scores on the ETS and GSP scales (r=-0.581, p=0.00).
Keywords: Phubbing; Students; Empathic Tendency